2012
DOI: 10.1098/rstb.2011.0238
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of ROOTLESS CONCERNING CROWN AND SEMINAL ROOTS, a LOB domain protein regulating shoot-borne root initiation in maize (Zea maysL.)

Abstract: Rootless concerning crown and seminal roots (Rtcs) encodes a LATERAL ORGAN BOUNDARIES domain (LBD) protein that regulates shoot-borne root initiation in maize (Zea mays L.). GREEN FLUORESCENT PROTEIN (GFP)-fusions revealed RTCS localization in the nucleus while its paralogue RTCS-LIKE (RTCL) was detected in the nucleus and cytoplasm probably owing to an amino acid exchange in a nuclear localization signal. Moreover, enzyme-linked immunosorbent assay (ELISA) experiments demonstrated that RTCS primarily binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 43 publications
3
78
0
Order By: Relevance
“…It has been demonstrated that LBD proteins can bind specifically to the 59-GCGGCG-39 LBD consensus sequence motif in the promoter of target genes (Husbands et al, 2007). It has been demonstrated that RTCS can bind to the LBD promoter element of arf34 that is located 277 bp upstream of the ATG start codon (Majer et al, 2012). Among the differentially expressed genes identified in this study, 100 of 828 contained at least one LBD motif in their 1-kb promoter.…”
Section: Distribution Of Lbd Promoter Motifs and In Vitro Interactionmentioning
confidence: 60%
See 4 more Smart Citations
“…It has been demonstrated that LBD proteins can bind specifically to the 59-GCGGCG-39 LBD consensus sequence motif in the promoter of target genes (Husbands et al, 2007). It has been demonstrated that RTCS can bind to the LBD promoter element of arf34 that is located 277 bp upstream of the ATG start codon (Majer et al, 2012). Among the differentially expressed genes identified in this study, 100 of 828 contained at least one LBD motif in their 1-kb promoter.…”
Section: Distribution Of Lbd Promoter Motifs and In Vitro Interactionmentioning
confidence: 60%
“…The maize LBD genes rtcs-neighbour (rtcn; GRMZM2G092483_T02; Taramino et al, 2007) and lbd34 (GRMZM2G075499_T01; Majer et al, 2012) are preferentially expressed in wild-type versus rtcs coleoptilar nodes at all three developmental stages dissected in this study. rtcn is physically located next to the rtcs gene in the maize genome (Taramino et al, 2007).…”
Section: Rtcs-dependent Regulation Of Lob Domain Genes and Transcriptmentioning
confidence: 62%
See 3 more Smart Citations